Generation of a Novel Rat Model of Angelman Syndrome with a Complete Ube3a Gene Deletion. Issue 3 (21st January 2020) - Dodge, Andie; Peters, Melinda M.; Greene, Hayden E.; Dietrick, Clifton; Botelho, Robert; Chung, Diana; Willman, Jonathan; Nenninger, Austin W.; Ciarlone, Stephanie; Kamath, Siddharth G.; Houdek, Pavel; Sumová, Alena; et al.
Abstract : Angelman syndrome (AS) is a rare genetic disorder characterized by severe intellectual disability, seizures, lack of speech, and ataxia. The gene responsible for AS was identified as Ube3a and it encodes for E6AP, an E3 ubiquitin ligase. Currently, there is very little known about E6AP's mechanism of action in vivo or how the lack of this protein in neurons may contribute to the AS phenotype. Elucidating the mechanistic action of E6AP would enhance our understanding of AS and drive current research into new avenues that could lead to novel therapeutic approaches that target E6AP's various functions. To facilitate the study of AS, we have generated a novel rat model in which we deleted the rat Ube3a gene using CRISPR. The AS rat phenotypically mirrors human AS with loss of Ube3a expression in the brain and deficits in motor coordination as well as learning and memory. This model offers a new avenue for the study of AS. Autism Res 2020, 13: 397–409 . © 2020 International Society for Autism Research, Wiley Periodicals, Inc. Lay Summary: Angelman syndrome (AS) is a rare genetic disorder characterized by severe intellectual disability, seizures, difficulty speaking, and ataxia. The gene responsible for AS was identified as UBE3A, yet very little is known about its function in vivo or how the lack of this protein in neurons may contribute to the AS phenotype. To facilitate the study of AS, we have generated a novel rat model in which we deleted the rat Ube3a gene using CRISPR. The AS rat mirrors human AS with loss of Ube3a expression in the brain and deficits in motor coordination as well as learning and memory. This model offers a new avenue for the study of AS.